Betaine prevents and reverses the behavioral deficits and synaptic dysfunction induced by repeated ketamine exposure in mice - Shao-Tsu Chen (Elsevier, 2021)
As an N-methyl-D-aspartate (NMDA) receptor inhibitor, ketamine has become a popular recreational substance and currently is used to address treatment-resistant depression. Since heavy ketamine use is associated with persisting psychosis, cognitive impairments, and neuronal damage, the safety of ketamine treatment for depression should be concerned. The nutrient supplement betaine has been shown to counteract the acute ketamine-induced psychotomimetic effects and cognitive dysfunction through modulating NMDA receptors. This study aimed to determine whether the adjunctive or subsequent betaine treatment would improve the enduring behavioral disturbances and hippocampal synaptic abnormality induced by repeated ketamine exposure. Mice received ketamine twice daily for 14 days, either combined with betaine co-treatment or subsequent betaine post-treatment for 7 days. Thereafter, three-chamber social approach test, reciprocal social interaction, novel location/object recognition test, forced swimming test, and head-twitch response induced by serotonergic hallucinogen were monitored. Data showed that the enduring behavioral abnormalities after repeated ketamine exposure, including disrupted social behaviors, recognition memory impairments, and increased depression-like and hallucinogen-induced head-twitch responses, were remarkably improved by betaine co-treatment or post-treatment. Consistently, betaine protected and reversed the reduced hippocampal synaptic activity, such as decreases in field excitatory post-synaptic potentiation (fEPSP), long-term potentiation (LTP), and PSD-95 levels, after repeated ketamine treatment. These results demonstrated that both co-treatment and post-treatment with betaine could effectively prevent and reverse the adverse behavioral manifestations and hippocampal synaptic plasticity after repeated ketamine use, suggesting that betaine can be used as a novel adjunct therapy with ketamine for treatment-resistant depression and provide benefits for ketamine use disorders.